Tales from the Himalayas: Straight from the Heart of Priyanka Pradhan - Antra Singh; Hampamma G (International Journal of Behavioral Sciences, 2024)
“Tales from the Himalayas” is a collection of seventeen short stories written by Priyanka Pradhan. She is the recipient of the “Ruskin Bond Promising Writer Award 2019” at the Dehradun Literature Festival. Each tale in the collection is an entertaining, heart-warming, and delightful read. Themes of family, friendship, belonging, and loss are prominent in the pages. The stories depict the rich cultural heritage that resides in the heart of the mountains. This paper attempts to study the characteristic features that define children’s literature using these tales as a retrospect. These stories can be read from the unique point of view of a child.They transport the readers to a psycho-social setting away from the urban land where there are snow leopards, ghosts, and the village monster. Contemporary children’s literature focuses on themes like nature, folk, culinary, moral values, gender, and self-love. The stories prioritize the interaction a child has with his/her parents, grandparents, teacher, and other members of society. They depict the prominent journey each child has to go through in the process of development. A colorful image accompanies each tale to attract young readers. The stories showcase the vibrant cultural heritage embedded in the heart of the mountains. This paper aims to analyze the defining characteristics of children’s literature through the lens of these tales. Presented from a child's perspective, these stories immerse readers in a psycho-social environment far removed from urban life, featuring elements like snow leopards, ghosts, and the village monster. Modern children’s literature often explores themes such as nature, folklore, culinary traditions, moral values, gender, and self-love.
Keywords: Short fiction; children’s literature; folk; priyanka pradhan; the great himalayan explorer